Pengaruh Kemampuan Fisik Terhadap Keterampilan smash Dalam Permainan Bulutangkis - Kamaruddin, Ilham (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2019)
This research is descriptive research that aims to determine : (1 ) the physical fitnes of athletes badminton , (2 ) skill smash athlete badminton , (3 ) physical fitnes contributed to the smash skill in badminton. The population is all the athletes PB.Yanti Jaya Makassar totaling 40 people . Sampling technique was purposive sampling . The data analysis technique used is descriptive analysis , correlation coefficient analysis , and single regression analysis through SPSS 14, at significant level α = 0.05 .  The results showed that: ( 1 ) the physical fitnes of in the category Enough with the average value of 200.05 , (2 ) Athlete Skills smash in the category Enough with the average value of 6.17 points ; ( 3 ) There is a significant analysis of the physical components of the skill smash on Athletes badminton , the R value of 0836 ( Pvalue < 0.05 ) and accounted for 69.8 %.